Population dynamics and management of aphids in vegetable ecosystem - Thamilvel D (Department of Agricultural Entomology, College of Agriculture, 2009)
Eight species of aphids viz., A. gossypii, A. craccivora, A. spiraecola, A. fabae, A. nerii, H. setariae, M. persicae and L. erysimi were recorded from 32 vegetables in a survey conducted in the four taluks of Thiruvananthapuram district of Kerala. Occurrence of A. gossypii on C. grandis, M. oleifera and P. tetragonolobus; A. craccivora on C. gladiata, P. tetragonolobus and S. grandiflora ; A. spiraecola on A. tricolor, C. sativus, C. tetragonoloba, M. oleifera, M. charantia, M. koeingii, P. tetragonolobus and S. androgynus ; M. persicae on A. tricolor and R. sativu; A. nerii on C. annuum and C. frutescens was recorded for the first time from the State and H. setariae on A. tricolor and A. dubius from South India. One hundred and twenty two other plants were identified as host plants of the different aphids. A. gossypii was the dominant species noted, closely followed by A. craccivora, and A. spiraecola. Maximum species of aphids were recorded on amaranthus followed by winged bean. Among the vegetables surveyed, chilli and coccinia were highly susceptible to A. gossypii and winged bean and cowpea to A. craccivora. Mosaic disease incidence was noted in 10 vegetables.